1994
DOI: 10.1128/jb.176.7.2068-2081.1994
|View full text |Cite
|
Sign up to set email alerts
|

Excision of a P4-like cryptic prophage leads to Alp protease expression in Escherichia coli

Abstract: The Escherichia coli K-12 alpA gene product, when overproduced from a multicopy plasmid, leads to suppression of the capsule overproduction and UV sensitivity phenotypes of cells mutant

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
124
2

Year Published

1996
1996
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(131 citation statements)
references
References 49 publications
5
124
2
Order By: Relevance
“…Phage integration target sequences also could be scanned for nearby sRNA genes. Many phage att sites overlap tRNAs (for review, see Campbell 1992), and ssrA, encoding the tmRNA, has a 3Ј structure like a tRNA and overlaps the att site of a cryptic prophage (Kirby et al 1994). In this work, we found that the 3Ј end and terminator of #14 overlaps the previously mapped phage P2 att site (Barreiro and Haggard-Ljungquist 1992).…”
Section: Evaluation Of Selection Criteriasupporting
confidence: 50%
“…Phage integration target sequences also could be scanned for nearby sRNA genes. Many phage att sites overlap tRNAs (for review, see Campbell 1992), and ssrA, encoding the tmRNA, has a 3Ј structure like a tRNA and overlaps the att site of a cryptic prophage (Kirby et al 1994). In this work, we found that the 3Ј end and terminator of #14 overlaps the previously mapped phage P2 att site (Barreiro and Haggard-Ljungquist 1992).…”
Section: Evaluation Of Selection Criteriasupporting
confidence: 50%
“…In E. coli, for instance, the growth defects of strains lacking SsrA are magnified at high temperatures or under carbon starvation (2,13), suggesting that quality assurance becomes more important when the incidence of translational errors is elevated. Other phenotypes of SsrA-defective E. coli include reduced motility (2), increased protease activity (14), defects in plating of phage immP22 and induction of temperature-sensitive lysogens of phage Mu (6,15), and increased levels of LacI, cI, and LexA repression (16).…”
mentioning
confidence: 99%
“…coli has also a rich repertoire of elements using the tmRNA gene for their integration site (Casjens, 2003). One of such elements is a P4-related cryptic prophage CP4-57, which locates at 60 min on the K-12 chromosome (Kirby et al, 1994;Retallack et al, 1994). In strain 781-55, the fllA 44 locus was found to be flanked by the yfjJ and yfjU genes, both of which locate within CP4-57 ( Fig.…”
Section: Discussionmentioning
confidence: 99%